2021
DOI: 10.1039/d1fo00641j
|View full text |Cite
|
Sign up to set email alerts
|

In vitro dipeptidyl peptidase IV inhibitory activity and in situ insulinotropic activity of milk and egg white protein digests

Abstract: Gastrointestinal digests of milk and egg white proteins inhibited DPP-IV activity. The absorbable fraction from the intestinal digests induced insulin secretion in BRIN-BD11 cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 33 publications
(56 reference statements)
1
2
0
Order By: Relevance
“…This is in keeping with the results obtained by Nongonierma et al, which evidenced the positive impact of the SGID on the DPP-IV inhibitory activity of a whey protein hydrolysate, for which the IC 50 measured in vitro after SGID was closed (1.02 ± 0.05 mg.mL -1 ) of the value obtained here for dWPH (1.28 ± 0.38 mg.mL -1 ) (44). The IC 50 values obtained here for the digested whey protein isolate (1.36 ± 0.55 mg.mL -1 ) with the intestinal cell-based in situ method are comparables with those we obtained (1.64 ± 0.11 mg mL −1 ) for dWPI in a precedent study and slightly higher than those obtained by Santos-Hernández et al (1.17 ± 0.09 mg mL −1 ) for a digested whey protein concentrate (45).…”
Section: Food and Function Accepted Manuscriptsupporting
confidence: 90%
See 1 more Smart Citation
“…This is in keeping with the results obtained by Nongonierma et al, which evidenced the positive impact of the SGID on the DPP-IV inhibitory activity of a whey protein hydrolysate, for which the IC 50 measured in vitro after SGID was closed (1.02 ± 0.05 mg.mL -1 ) of the value obtained here for dWPH (1.28 ± 0.38 mg.mL -1 ) (44). The IC 50 values obtained here for the digested whey protein isolate (1.36 ± 0.55 mg.mL -1 ) with the intestinal cell-based in situ method are comparables with those we obtained (1.64 ± 0.11 mg mL −1 ) for dWPI in a precedent study and slightly higher than those obtained by Santos-Hernández et al (1.17 ± 0.09 mg mL −1 ) for a digested whey protein concentrate (45).…”
Section: Food and Function Accepted Manuscriptsupporting
confidence: 90%
“…44 The IC 50 values obtained here for the digested whey protein isolate (1.36 ± 0.55 mg mL −1 ) with the intestinal cell-based in situ method are comparable with those we obtained (1.64 ± 0.11 mg mL −1 ) for dWPI in a precedent study and slightly higher than those obtained by Santos-Hernández et al (1.17 ± 0.09 mg mL −1 ) for a digested whey protein concentrate. 45…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, Caron et al [ 42 ] found an IC 50 for hemoglobin protein (1.6 mg·mL −1 ), which is relatively close to the IC 50 found in this study (2.8 ± 0.4 mg·mL −1 ). Similarly, Theysgeur et al [ 33 ] reported an IC 50 of 3.7 mg·mL −1 for a hydrolyzed fish by-product, while Santos-Hernández et al [ 50 ] found an IC 50 value of 1.17 mg·mL −1 for whey protein digests, 0.87 mg·mL −1 for casein digests, and 1.75 mg·mL −1 for egg white digests using the same cell-based method. Rivero-Pino et al [ 27 ] found an IC 50 of 2.93 mg·mL −1 for pea protein using an in vitro model.…”
Section: Discussionmentioning
confidence: 96%